Elemental composition of wild colisa lalia in relation to body size and condition factor from Pakistan - Fatima, Summera; Naeem, Muhammad (International Journal of Biological Research, 2016)
Twenty three samples of wild fish Colisa lalia were collected from Nala Daik, a stream in Sialkot. The concentration of Cadmium (Cd), Cobalt (Co), Iron (Fe), Manganese (Mn) and Nickel (Ni) in the whole fish were determined by Flame atomic absorption spectrophotometer to estimate the water contamination and health risk of human consumption in Sialkot region which is a popular industrial area. The detected cobalt in twenty two samples and nickel in eight samples exceeds the permitted limits for fish set by IAEA-407 (Wyse et al. 2003).While the concentration of Cadmium, Iron and Manganese in all samples were below permitted level set by European and other International Organizations. The concentration of Cd, Co, Fe, Mn and Ni was ranging from 0.20-1.71, 0.84-55.38, 82.82-137.63, 1.61-22.73, 2.23-5.98 having mean value as 0.67, 39.31, 139.09, 13.26 and 0.56 (ug/g wet weight) respectively. Regressions analysis was performed for both size and condition factor with metal concentrations. As far as correlation with total length and weight was concerned, a decreasing trend was shown by Cd and Ni while Co, Fe and Mn showed an increasing trend and these correlations were found significant for all these elements. No effect of condition factor was observed in the study on Colisa lalia. Inter-elemental regression showed significant correlations among metals.